Analysis of Protection and Recovery Efforts for Domestic Violence (KDRT) Victims, Especially Children and Women - Sakba, Azhar; Kusuma, Sheila (Universitas Islam Negeri Sumatera Utara, 2022)
Domestic violence is a form of criminal act that can be subject to sanctions in the form of imprisonment or imprisonment as well as the impact it has on the victim. Domestic violence can be committed by one family member against another family member. Talking about violence is no longer taboo. The motive for domestic violence is often caused by disharmony in family relationships, economic problems, poor communication and so on. These various forms of violence have negative impacts on the victims, including psychological, mental and physical impacts carried out directly or indirectly by the perpetrators of domestic violence. The impacts caused by violence not only have an impact in the short term but also in the long term.